Francis Bacon - Hammer, Martin (Phaidon, 2013)
The art of Francis Bacon (1909-1992) epitomises the angst at the heart of the modern human condition. His dramatic images of screaming figures and distorted anatomies are painted with a richly gestural technique, alluding to such old masters as Titian, Velazquez and Rembrandt. Displaying repressed and raw emotion, his body of work includes portraits of Lucian Freud and John Deakin.